Mechanistic study on the restoration of intestinal barrier integrity and alleviation of inflammatory bowel disease by rhynchophylline via the AhR-NR4A1 pathway - Mao, Xuwen; Cheng, Lufeng; Liu, Yu; Wu, Yuche (Frontiers in Pharmacology, 2025)
BackgroundRestoring intestinal barrier function is considered an effective strategy for the treatment of Inflammatory Bowel Disease (IBD). Rhynchophylline (Rhy), a bioactive alkaloid sourced from the traditional herbs Uncariarhynchophylla used in Chinese medicine, is known for its antihypertensive, anti-asthmatic, and antitumor properties. This study explores the pharmacological effects and molecular mechanisms of Rhy in treating IBD.MethodsIn vitro cell inflammation injury model was established, and the inflammatory factors, cell permeability, cell proliferation, and intercellular tight junction protein expression were measured after Rhy intervention, which verified the anti-inflammatory activity and enhancement of intestinal barrier function of Rhy. In vivo animal model of acute and chronic colitis was established, and Rhy was administered orally at three dose levels to evaluate the protective effects of Rhy on acute and chronic colitis in animals. The signaling pathways that enhance the intestinal barrier function of Rhy were identified through transcriptomics, gene knockout techniques, and molecular dynamics simulations.ResultsIn vitro results indicate that the levels of inflammatory markers–including IL-6, TNF-α, and NO–can be decreased by Rhy, demonstrating anti-inflammatory activity. It significantly lowers cellular permeability, promotes the proliferation of intestinal epithelial cells, and upregulates the expression of tight junction proteins Claudin4, Occludin, and ZO-1. These effects improve cellular morphology and improve the robustness of the intestinal barrier. In vivo, using three types of colitis animal models, Rhy shows significant protective effects on mice with acute and chronic colitis. It markedly reduces weight loss and Disease Activity Index (DAI) scores, prevents colonic shortening, reduces intestinal permeability, and decreases serum levels of IL-6, TNF-α, CXCL1, and IL-1β. These effects restore the structural integrity of colonic tissues and alleviate symptoms of acute and chronic colitis. Additionally, Rhy activates the AhR-NR4A1 pathway. This activation upregulates Claudin4, Occludin, and ZO-1 to repair the intestinal barrier and exert anti-colitic effects.ConclusionThese findings highlight Rhy improve the function and inhibits inflammation, providing dual beneficial activities in the epithelial lining of the gut to prevent and treat colitis.